Políticas de fidelização dos estudantes na educação superior: Um estudo do Unilasalle Canoas/RS - Silva, Paulo César Azevedo (2014)
This dissertation is characterized by being a qualitative research of case study type. The central research question is: how are the policies of retaining the loyalty of students in Higher Education: a study of the Unilasalle Canoas RS. The research aims to analyze the policy of customer loyalty of undergraduate students of the Centro Universitário La Salle Canoas RS - Brazil, in the period 2010-2013. The data collection instruments are: documentary analysis and questionnaire. The survey subjects were the Unilasalle graduating students of the first semester of 2014. The data analysis was a content analysis proposed by Bardin. This process resulted in 6 categories: 1) IES funding policy; 2) curriculum linked to the market and life; 3) demand for active methodologies; 4) the student is a person who complains for link; 5) differentiated physical spaces: teaching and learning beyond the classroom; 6) academic management close to the student. Finally, proposals will be presented to enable the effective retaining of loyalty of students in Higher Education, for understanding that it means to go beyond access and even of permanence.